Determinant factors for early weaning - Lima, Amanda de Oliveira; Meneghin, Izadora Fogare; Wichoski, Cleusa (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Nutrição, 2022)
Breastfeeding is the exclusive food for the child in the first six months of age, and nutritional and immunological benefits are provided to the baby. However, some factors can influence early weaning. The objective of this work was to identify the main factors responsible for the interruption of exclusive breastfeeding (EB), through questionnaires related to socioeconomic, cultural and dietary characteristics. It is a cross-sectional, quantitative, descriptive, explanatory and observational survey, through an online questionnaire (Google® Forms). 574 women participated in the survey, of which the majority claimed to have completed higher education. The family income range of 1–2 minimum wages was predominant among these women, regardless of their occupational activity. Most women of the interviewed age groups did not receive breastfeeding guidelines, seeking information through social media. There was a prevalence in the introduction of other milks before 6 months by mothers under 40 years of age. The term of EB of 6 months or more was predominant among mothers with lower family income, housewives and who did not introduce bottles or pacifiers. Approximately 95.6% think that the family's eating habits have an influence on the child's diet, and fruits were the first most offered food after 6 months. Women under the age of 21 were more concerned and influenced by information related to EB. Therefore, the level of education, family income, age, work, guidance on breastfeeding, use of bottles or pacifiers and family eating habits had an important influence on the interruption of EB. Knowledge of the factors is essential to alleviate and avoid early weaning.